Pengaruh Ukuran Perusahaan, Pertumbuhan Perusahaan, Profitabilitas, Dan Likuiditas Terhadap Struktur Modal Pada Perusahaan Sektor Kesehatan Yang Terdaftar Di BEI Tahun 2018-2022 - Syarifah Ratih Kartika Sari; Marta Swastika Hani Safira; Djuwitawati Ratnaningtyas (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of company size, company growth, profitability, and liquidity on the company's capital structure. The technique in sampling uses purposive sampling method. Data obtained from secondary data annual reports of 15 companies engaged in the health sector listed on the IDX in 2018, 2019, 2020, 2021, and 2022. Data analysis was carried out by multiple linear regression with the SPSS version 25 for windows program. The results of hypothesis research show that the company size independence variable is 0.002, the company growth independence variable is 0.946, the profitability independence variable is 0.000 and the liquidity independence variable is 0.000. With these results it can be stated that company growth has no significant effect, while company size, profitability and liquidity have a significant effect.